Fetal lung volume in congenital diaphragmatic hernia. Issue 5 (1st February 2006) - Bonfils, M; Emeriaud, G; Durand, C; Brancato, S; Nugues, F; Jouk, P-S; Wroblewski, I; Debillon, T
Abstract : In a retrospective study of 22 neonates with congenital diaphragmatic hernia, fetal lung volume (FLV) measured by magnetic resonance imaging was associated with survival; the best FLV ratio cut-off to predict mortality was 30% of expected FLV. This study supports a correlation between FLV and the chances of survival.